Quasi-biennial oscillation: laboratory experiments - Semin, Benoît; Pétrelis, François (Comptes Rendus. Physique)
The quasi-biennial oscillation (QBO) is an oscillation of the wind in the equatorial stratosphere. This wind is a mean flow induced by atmospheric waves, including internal gravity waves, which explain that the period (28 month) is not linked to any astrophysical forcing. This oscillation has only been reproduced in 3 laboratory experiments, which share a similar geometry. We present the details of our experimental set-up, and we explain which improvements allowed us to obtain quantitative measurements during long times. We show experimentally the feedback of the mean flow on the waves, which is one of the key ingredient of the oscillation. The details of the analytical resolution of the 1D model of Plumb and McEwan are given. We compare experimental results to analytical and numerical results, and found a qualitative agreement. The period decreases when the forcing increases, and the amplitude of the mean flow is not monotonic with respect to height and displays two local maxima as a function of height close to the threshold. The bifurcation is always a Hopf one, but can be subcritical or supercritical depending on the dominant dissipation mechanism of the mean flow which can be tuned experimentally by changing the Brunt–Väisälä frequency. We argue that an investigation of the bifurcation in general circulation models (GCM) is of interest to better understand the evolution of the QBO due to climate change.